Adipokines in atherosclerosis: unraveling complex roles - Luo, Jiaying; He, Zhiwei; Li, Qingwen; Lv, Mengna; Cai, Yuli; Ke, Wei; Niu, Xuan; Zhang, Zhaohui (Frontiers in Cardiovascular Medicine, 2023)
Adipokines are biologically active factors secreted by adipose tissue that act on local and distant tissues through autocrine, paracrine, and endocrine mechanisms. However, adipokines are believed to be involved in an increased risk of atherosclerosis. Classical adipokines include leptin, adiponectin, and ceramide, while newly identified adipokines include visceral adipose tissue-derived serpin, omentin, and asprosin. New evidence suggests that adipokines can play an essential role in AS progression and regression. Here, we summarize the complex roles of various adipokines in AS lesions. Representative protective adipokines include adiponectin and neuregulin 4; deteriorating adipokines include leptin, resistin, thrombospondin-1, and C1q/tumor necrosis factor-related protein 5; and adipokines with dual protective and deteriorating effects include C1q/tumor necrosis factor-related protein 1 and C1q/tumor necrosis factor-related protein 3; and adipose tissue-derived bioactive materials include sphingosine-1-phosphate, ceramide, and adipose tissue-derived exosomes. However, the role of a newly discovered adipokine, asprosin, in AS remains unclear. This article reviews progress in the research on the effects of adipokines in AS and how they may be regulated to halt its progression.